Posted by Veronica on Tuesday, November 10, 2009 at 5:31pm.
I think you mean
(√(4x))^4 + 8x^3 - 13x^2 - 2x + 3
16x^2 + 8x^3 - 13x^2 - 2x + 3
= 8x^3 + 3x^2 - 2x + 3
Now what about it?
What do want done with it?
I need the roots of 4x^4+8x^3-13x^2-2x+3
Read your first line, can you see how it can be misinterpreted?
f(x) = 4x^4+8x^3-13x^2-2x+3
try x = ±1, ±3
f(1) = 0, so x-1 is a factor,
I then used synthetic division to show that
4x^4+8x^3-13x^2-2x+3 = (x-1)(4x^3 + 12x^2 - x - 3)
but (4x^3 + 12x^2 - x - 3)
= 4x^2(x+3) - (x+3)
= (x+3)(4x^1 - 1)
4x^4+8x^3-13x^2-2x+3 = 0
(x-1)x+3)(2x+1)(2x-1) = 0
x = 1, -3, ±1/2
college - let i = the square root of -1 with i to the 1st power =i, i to the 2nd...
Algebra - Factor each of following expressions x (4th power) - x (3rd power) - ...
math - what is (x to the 3rd power + x to the 2nd power) divided by ((x+4)(X-4...
algebra - how do I evaluate 2x to the 4th power + 2 x to the 3rd power + x to ...
math - (8x to the 3rd power) (4x to the 2nd power) simplifi
Math/Standard and scientific notation - Express each measure in standard form. (...
Math - Write the following number in standard form (4X10 4th power)+(3X10 3rd ...
math - The question that have is to simplify and write the answer in ...
Algebra II - The problem states: Saturn is approximately 1.4x 10 to the 9th ...
algebra - 7s over 5t to the negative 3rd power 2 to the negative 3rd power times...
For Further Reading